2015
DOI: 10.1016/j.rse.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A new vegetation index for detecting vegetation anomalies due to mineral deposits with application to a tropical forest area

Abstract: This study aimed at developing a geobotanical remote sensing method to explore mineral deposits in areas covered by thick vegetation. For this, a new vegetation index (VI) is proposed using reflectance data from five bands in the visible green to shortwave infrared region. This index is called VIGS (Vegetation Index considering Greenness and Shortwave infrared), developed so that the VI can accurately detect vegetation stress caused by metal contamination of soils. A set of laboratory experiments was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…In recent years, many vegetation indexes have been developed (Zarcotejada, Miller, Noland, Mohammed, & Sampson, ; Maire, François, & Dufrene, ; Haboudanem, Tremblay, Miller, & Vigneault, ; Vincini, Frazzi, & Alessio, ; Ziosi et al, ;). Using such indices, 22 varieties index of Longjing fresh tea have been classified (Gamon, Penuelas, & Field, ; Gitelson, Kaufman, Stark, & Rundquist, ; Hede, Kashiwaya, Koike, & Sakurai, ; Huete, ; Huete et al, ; Kaufman & Tanre, ; Penuelas, Filella, Biel, Serrano, & Save, ; Rondeaux, Steven, & Baret, ; Roujean & Breon, ; Shi, Wang, Liu, & Wu, ; Sims & Gamon, ). These indexes were divided into five categories according to combination form, which are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, many vegetation indexes have been developed (Zarcotejada, Miller, Noland, Mohammed, & Sampson, ; Maire, François, & Dufrene, ; Haboudanem, Tremblay, Miller, & Vigneault, ; Vincini, Frazzi, & Alessio, ; Ziosi et al, ;). Using such indices, 22 varieties index of Longjing fresh tea have been classified (Gamon, Penuelas, & Field, ; Gitelson, Kaufman, Stark, & Rundquist, ; Hede, Kashiwaya, Koike, & Sakurai, ; Huete, ; Huete et al, ; Kaufman & Tanre, ; Penuelas, Filella, Biel, Serrano, & Save, ; Rondeaux, Steven, & Baret, ; Roujean & Breon, ; Shi, Wang, Liu, & Wu, ; Sims & Gamon, ). These indexes were divided into five categories according to combination form, which are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…For a Landsat ETM+ image, G , R , N , S 1 , and S 2 correspond to the reflectance at bands 2, 3, 4, 5, and 7, respectively. The w 1 , w 2 , w 3 , and w 4 are weights for each term and a combination of w 1 = 1.0, w 2 = 0.5, w 3 = 1.5, and w 4 = 1.5 was employed in this study based on our previous result [ Hede et al ., ]. Equation of NDVI is: NDVI=NRN+R …”
Section: Methodsmentioning
confidence: 99%
“…To emphasize a reflectance change caused by the stress and clarify the spatial pattern of anomalies, a ratio of the mean ( m ) to the standard deviation ( σ ) calculated on a per‐pixel basis from the VIGS data set was used. Selection of this ratio was founded on our previous studies that showed that the VIGS values tended to be large at metal contamination zones common to the Landsat images in the growing season [ Hede et al ., ]. The present five images were within this season.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are based on the optical properties of plants and can be used for identifying nutrient deficiencies, plants diseases, water stress and excess water, insect damage, weeds, etc. (Baret, 2016;Haboudane, Miller, Pattey, Zarco-Tejada, & Strachan, 2004;Hede, Kashiwaya, Koike, & Sakurai, 2015;Sankaran et al, 2010). Combination of plant knowledge and remote sensing data can provide information for plant management and even initial advices about plant stress to prevent the spread of disease or pest infestation by adopting appropriate reactions in the early stages of stress.…”
Section: Introductionmentioning
confidence: 99%